IDENTIFIKASI PUSAT PELAYANAN DI KABUPATEN BANGKALAN DENGAN METODE SKALOGRAM - Kurniyati Indahsari (Trunojoyo University of Madura, 2009)
This article describes the result of public service center assessment and recommendation for public service providing in Bangkalan District. Skalogram method is used to rank sub-districts in Kabupaten Bangkalan based on kinds and a number of public service facilities. The identification showed that center of public services is located in 4 of 6 sub districts, which is determined as Sub Satuan Wilayah Pembangunan (Sub Region of Development Unit) or kecamatan pusat ordo IV (ordo IV of sub municipal's center) in Rencana Tata Ruang Wilayah Kabupaten Bangkalan (Bangkalan's masterplan of regional development) 1999-2009. More over, the location of public facilities center is not the same as location of population center. Therefore, it's recommended to accelerate the providing of public service facilities in sub districts which are determined as Sub Satuan Wilayah Pembangunan (Sub Region of Development Unit) or kecamatan pusat ordo IV (ordo IV of sub municipal's center) in Rencana Tata Ruang Wilayah Kabupaten Bangkalan (Bangkalan's masterplan of regional development) 2009-2029, especially in Klampis and Tanah Merah, and which are predicted as location of population centers, i.e. Arosbaya, Socah, Tanah Merah, Kwanyar and Klampis.The results of the study are : (1) Four of the six sub municipal (kecamatan) center of ordo IV have become a higher public center service compare to others sub municipal (kecamatan); (2) Ideal condition, in which public service center should be located around the center of population (highest population density) area, is not met. Hence it is suggested to prioritize the process of providing the needed quality and quantity of infrastructure for public service at kecamatan (sub municipal) of Klampis and Tanah Merah as well as kecamatan (sub municipal) that is predicted to have a high population density in the future but still have a relatively low hierarchy of public service center today i.e.: Arosbaya, Socah, Tanah Merah, Kwanyar dan Klampis.